2006
DOI: 10.1111/j.1365-2745.2006.01126.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐organized vegetation patterning as a fingerprint of climate and human impact on semi‐arid ecosystems

Abstract: Summary1 Spatially periodic vegetation patterns are well known in arid and semi-arid regions around the world. 2 Mathematical models have been developed that attribute this phenomenon to a symmetry-breaking instability. Such models are based on the interplay between competitive and facilitative influences that the vegetation exerts on its own dynamics when it is constrained by arid conditions, but evidence for these predictions is still lacking. Moreover, not all models can account for the development of regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
184
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(203 citation statements)
references
References 45 publications
(61 reference statements)
6
184
0
7
Order By: Relevance
“…An important example is related to the suggestion that transitions from scale-free patterns to patterns with characteristic length scales may serve as warning signals for imminent desertification (Kéfi et al 2007a), and that such transitions can be identified by monitoring changes in patch statistics (Manor & Shnerb 2008a). As the time scale of such changes can be quite long (tens of years in the case of woody vegetation; Barbier et al 2006), faster indicators are needed. Estimates of the likelihood of a given region to support scale-free patterns, based on soil properties and species traits, can be made in a relatively short time, and may provide such indicators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important example is related to the suggestion that transitions from scale-free patterns to patterns with characteristic length scales may serve as warning signals for imminent desertification (Kéfi et al 2007a), and that such transitions can be identified by monitoring changes in patch statistics (Manor & Shnerb 2008a). As the time scale of such changes can be quite long (tens of years in the case of woody vegetation; Barbier et al 2006), faster indicators are needed. Estimates of the likelihood of a given region to support scale-free patterns, based on soil properties and species traits, can be made in a relatively short time, and may provide such indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Vegetation patchiness affects the distribution of limiting resources and seeds, modifies species distribution and diversity, and may contain information about imminent catastrophic shifts such as desertification (Kéfi et al 2007a;Shachak et al 2008). Field observations have revealed two contrasting types of vegetation landscapes: nearly periodic vegetation patterns with characteristic length scales, such as bands on hill slopes or spotted patterns (Valentin et al 1999;Barbier et al 2006), and scale-free patterns that lack characteristic length scales and follow broad, power-lawlike patch-size distributions (Kéfi et al 2007a;Scanlon et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Such mechanisms can generate any unstable uniform state, and thence patterns. However, for semiarid vegetation a uniform state can only lose stability via changes in environmental parameters such as rainfall (35,36), which are inherently gradual. Therefore, marginally stable uniform states can occur, but those that are fully unstable cannot.…”
Section: Pattern Generation From Uniform Vegetationmentioning
confidence: 99%
“…Fig. 1a) is symmetry-breaking in the strict sense (Barbier, 2006;Barbier et al, 2006Barbier et al, , 2008. As such, this instability can occur in the absence of slope-induced water redistribution, a mechanism that has long been thought to be primordial for vegetation pattern formation (Tongway et al, 2001).…”
Section: Introductionmentioning
confidence: 99%